INTERAKSI SOSIAL ANAK KORBAN EKSPLOITASI DIKAWASAN MARPOYAN - Novita Sari; Tri Umari; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to identify and clearly describe the profile and social interactions of child victims of exploitation in the Marpoyan area. The subjects of this study were five children of exploitation victims. The research method used a qualitative approach with descriptive research type. Data collection techniques in the form of observation and interviews. Data analysis techniques used in this study were data collection, data reduction, data presentation, and conclusions. Profiles of children victims of exploitation in the Marpoyan area aged 5 to 12 years, who work as a fried food seller and newspaper seller. Four out of five children victims of exploitation still live with complete parents and one child only lives with the father. The five children who are victims of exploitation are no longer in school. The social interactions of children victims of exploitation in the Marpoyan area are interactions that exist in the form of cooperation, competition, accommodation and assimilation, as well as conflicts / disputes that have gone well. There is no significant competition and conflict in the interaction of child victims of exploitation in the Marpoyan area. The dominant aspects that occur in the interaction of child victims of exploitation in the Marpoyan area are cooperation, accommodation and assimilation.Key Words: Profile, Social Interaction, Child Victims of Exploitation.